Ventral Prostate Fibrosis in the Akita Mouse Is Associated with Macrophage and Fibrocyte Infiltration - Sanghee Lee; Guang Yang; William Mulligan; Jerry Gipp; Wade Bushman (Journal of Diabetes Research)
A higher incidence of lower urinary tract symptoms (LUTS) among diabetic men is unexplained. Recently, prostate inflammation and fibrosis have been implicated as major contributing factors to bladder outlet obstruction and LUTS. We characterized the inflammatory cell infiltrate and collagen content of the anterior, dorsal, and ventral lobes of 18-week-old DBA2J.Ins2-Akita mice (Akita) and age-matched control mice. We performed hematoxylin and eosin staining to score tissue injury and inflammation, picrosirius red staining to quantitate collagen content, and immunostaining to identify monocytes/macrophages and infiltrating fibrocytes. We observed significantly greater numbers of monocytes/macrophages and fibrocytes specifically in the ventral prostate of the Akita mice and found that this was associated with significant greater collagen content specifically in the ventral prostate of the Akita mice. These observations support the inference that diabetes elicits monocyte/macrophage infiltration and collagen accumulation in the prostate and suggest that further study of Akita mice may inform translational studies of diabetes in the genesis prostatic inflammation, prostatic fibrosis, and LUTS.